Diagnostic and Predictive Recurrence Value of Plasma Fibrinogen in Patients With Adrenocortical Carcinoma - Chengquan Ma; Bin Yang; Quanzong Mao (Clinical Medicine Insights: Oncology)
Background: The correlation between fibrinogen levels and adrenocortical carcinoma (ACC) remains unclear. This study aimed to explore the value of preoperative plasma fibrinogen as a biomarker for ACC. Methods: We identified 40 patients with ACC and 170 patients with adrenal adenoma (AA) who underwent surgery at our institution between 2015 and 2022. Plasma fibrinogen levels and postoperative tumor recurrence information of the patients were also recorded. For intergroup comparisons, data obtained from the AA and ACC groups were evaluated using a t -test. The cutoff value of fibrinogen level was determined using a receiver operating characteristic (ROC) curve. Results: Mean fibrinogen levels in the AA and ACC groups were 2.81 ± 0.59 g/L and 3.88 ± 1.75 g/L, respectively ( P  < .001). Fibrinogen level, which can help distinguish between AA and ACC, was evaluated using the ROC curve. The cutoff fibrinogen level was estimated as 3.87 g/L according to the Youden index. With this value, the sensitivity was 62.5%, specificity was 95.7%, and the area under the ROC curve (AUC) was 0.74 ( P  < .001). Fibrinogen level, which can help distinguish between recurrence and non-recurrence, was evaluated using the ROC curve. The cutoff fibrinogen level was estimated as 3.96 g/L according to the Youden index. The sensitivity, specificity, and AUC were 90%, 71.4%, and 0.85, respectively ( P  < .001). Conclusion: According to the data in this study, plasma fibrinogen could be used to distinguish ACC from AA. Most importantly, plasma fibrinogen may be used to identify recurrence of postoperative ACC.